Comparative analysis of protein and differential responses of defense-related gene and enzyme activity reveals the long-term molecular responses of sugarcane inoculated with Sporisorium scitamineum. Issue 1 (1st January 2021) - Singh, Pratiksha; Singh, Rajesh Kumar; Song, Qi-Qi; Li, Hai-Bi; Guo, Dao-Jun; Malviya, Mukesh K.; Verma, Krishan K.; Song, Xiu-Peng; Lakshmanan, Prakash; Yang, Li-Tao; Li, Yang-Rui
ABSTRACT: Smut, the most important sugarcane fungal disease in China, is caused by Sporisorium scitamineum . Smut infection causes severe cane and sugar yield loss. Whole-plant resistance response is characterized by the expression of a large number of pathogenesis-related proteins and genes. Here, proteomic analysis by isobaric tag for relative and absolute quantification was conducted to identify differentially expressed proteins of two sugarcane varieties with contrasting resistance to smut, i.e. Yacheng71-374 (smut-susceptible) and GT29 (smut-resistant) following S. scitamineum infection. A total of 125 and 290 proteins were found differentially expressed after whip appearance in Yacheng71-374 and GT29 sugarcane varieties. Increased up-regulation of peroxidase and catalase and proteins involved in photosynthesis, calcium signaling, abscisic acid biosynthesis, and protein metabolism, were observed in GT29 as compared to Yacheng71-374, suggesting their potential involvement in smut defense mechanism(s) in sugarcane. The expression level of five important defense-related enzymes i.e. chitinase, glucanase, catalase, superoxide dismutase, and phenylalanine ammonia-lyase was analyzed by RT-qPCR. The expression of these enzymes was found enhanced considerably in GT29 as compared to Yacheng71-374 for up to six months following pathogen infection. These results provide new molecular insights into long-term responses of sugarcane to smut infection, a much over-looked aspect of sugarcane smut disease.